2015
DOI: 10.5194/amt-8-171-2015
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric assimilation of radio occultation and ground-based GPS data using non-stationary background model error covariance

Abstract: Abstract. Ionospheric data assimilation is a powerful approach to reconstruct the 3-D distribution of the ionospheric electron density from various types of observations. We present a data assimilation model for the ionosphere, based on the Gauss-Markov Kalman filter with the International Reference Ionosphere (IRI) as the background model, to assimilate two different types of slant total electron content (TEC) observations from ground-based GPS and space-based FORMOSAT-3/COSMIC (F3/C) radio occultation. Covar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 31 publications
(30 reference statements)
1
45
0
Order By: Relevance
“…normalΔUhm()t+normalΔt=adjUhm()t+normalΔtUhm()t+normalΔt,which is only available at h m F 2 , vertically along the magnetic field line using a stationary correction given by the following Gaussian function ( G ) as G()l=normalexp()lhmF222c2. G is computed along the field line ( l ), and the center of G is located at h m F 2 . Since the major empirical orthonormal functions computed from density profiles of the International Reference Ionosphere model show that the width of the ionospheric main layer is about 200 km [ Lin et al ., ], c is given as 100 km. U ∥ is modified by Uhm mainly within the F 2 layer at the time step t + Δ t .…”
Section: Methodsmentioning
confidence: 99%
“…normalΔUhm()t+normalΔt=adjUhm()t+normalΔtUhm()t+normalΔt,which is only available at h m F 2 , vertically along the magnetic field line using a stationary correction given by the following Gaussian function ( G ) as G()l=normalexp()lhmF222c2. G is computed along the field line ( l ), and the center of G is located at h m F 2 . Since the major empirical orthonormal functions computed from density profiles of the International Reference Ionosphere model show that the width of the ionospheric main layer is about 200 km [ Lin et al ., ], c is given as 100 km. U ∥ is modified by Uhm mainly within the F 2 layer at the time step t + Δ t .…”
Section: Methodsmentioning
confidence: 99%
“…While the applications based upon GPS/GNSS require knowledge of TEC, dual‐frequency GPS receivers have transformed the scenario of ionospheric observations from a single station or sparse measurements to global and high‐resolution measurements [ Lin et al , ]. Beginning with a modest number of 60 GPS receivers, the International GNSS Service (IGS) [ Zumberge et al , ] has now become a prime organization managing almost 400 GPS receivers as of now (see http://www.igs.org).…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [2015] developed a location-dependent background correlation model by using sample statistics from an ensemble of model outputs, and they suggested that this model can yield considerably higher quality assimilation analysis than the Gaussian function correlation model. Lin et al [2015] developed a location-dependent background correlation model by using sample statistics from an ensemble of model outputs, and they suggested that this model can yield considerably higher quality assimilation analysis than the Gaussian function correlation model.…”
Section: Observation and Background Error Covariancementioning
confidence: 99%